The Influence of Audio Visual Media on Interest in Participating Classical Services of Grade X Students - Humairha Fajriani; Mori Dianto; Triyono (Journal of Practice Learning and Educational Development, 2026)
This research is motivated by the low interest of students in participating in classical guidance services at school, which are generally still dominated by lecture methods so that they are considered monotonous and less interesting. Audio visual media is present as an alternative to create services that are more interactive, communicative, and in accordance with the development needs of students in the digital era. The objectives of this study are 1) To describe audio visual media in classical services, 2) To describe students' interest in participating in classical services, 3) To test the effect of audio visual media on the interest in participating in classical services of class X students at SMA Negeri 2 Pasaman. The type of research used is a quantitative descriptive method. The study population was all class X students of SMA Negeri 2 Pasaman, totaling 281 students, with a sample of 166 students selected using proportional random sampling techniques. The instrument used in this study was a questionnaire. To analyze the data, a simple linear regression formula was used. The results of the study obtained: 1) The selection of using audio visual media is in the appropriate category 2) The description of interest in participating in classical services is in the very appropriate category 3) There is a significant influence between the selection of using audio visual media on the interest in participating in classical services in class X of SMA Negeri 2 Pasaman. Based on the findings of this study, the researcher recommends that guidance and counseling teachers be able to increase the use of audio visual media for students so that they have an interest in participating in classical services.